Positive accounting theory: effect of accounting decision on earnings based bonus scheme of managers / Zuraini Ismail - Ismail, Zuraini (1992)
Earnings-based bonus scheme is a popular method of rewarding corporate executives in most of the largest US manufacturing corporation. The bonus plan is largely based on accounting earnings. Is it popular in Malaysia ? The feedback received from the Annual Asian Executive Corporation Survey shows that forty-five percent of the respondents mentioned would prefer to be paid with bonus and thirty-six percent opting for more benefits.